The treatment of polycystic ovary syndrome and systematization of knowledge - literature review - Cyboran, Katarzyna; Płaczek, Alicja; Machaj, Dominik; Siedlak, Agnieszka; Pondel, Kamil (Journal of Education, Health and Sport, 2022)
Polycystic ovary syndrome (PCOS) is a known disease among endocrinologists and gynecologists. The aforementioned disease entity affects up to six to twelve percent of women of reproductive age. [1] In 2017, the incidence among women of childbearing age was 82.44 per 100,000 population. A decade ago, it was 1.45% lower.[2] PCOS is a disease in which we have abnormal hormone levels. The result may be a problem with regular menstruation, problems with becoming pregnant, acne or excessive body weight. [3] Most often, patients arediagnosed only when complications occur. It is closely related to asignificant reduction in living standards. There are problems such as hair loss, acne and infertility.